DeepGreen – Metadata Schema for the exchange of publications between publishers and open access repositories. Version 1.1. June 2016 - Putnings, Markus; Dierkes, Thomas; Söllner, Konstanze; Goltz, Julia Alexandra; Bertelmann, Roland; Ceynowa, Klaus; Christof, Jürgen; Heidrich, Regina; Höhnow, Tobias; Kassube, Michael; Kuberek, Monika; Landes, Lilian; et al. (2016)
In 2011, important priorities were set to realize green publications in the open access movement in Germany. With financial support from the German Research Foundation (DFG), libraries negotiated Alliance licenses with publishers that guarantee extensive open access rights. Authors of institutions, that have therewith access to licensed journals, can freely publish their articles immediately or after a short embargo period in a repository of their choice. However, authors hesitantly use these open access rights. Also libraries – as managers of institutional and subject based repositories and thus legitimated representatives for the authors – only rarely make use of these rights. The aim of DeepGreen is to make the majority of those publications available online. Together with publishers of the Alliance licenses, the project consortium wants to develop a nearly fully automated workflow that covers both the delivery of data, including the full texts, of the publishers, as well as the data transformation to the necessary import formats and the loading process into the repositories. An intermediate “publication router” will serve as a distribution platform. The DeepGreen metadata schema contains metadata properties describing a wide range of deliverable bibliographic metadata from the Alliance license publishers (most common standards are JATS and CrossRef XML) as well as its compliance with technical, quality and metadata standards of the repositories. The schema includes required metadata elements and optional properties providing additional information.The metadata schema is aligned to the OCLC repository best practices (“Best Practices for CONTENTdm and other OAI-PMH compliant repositories: creating sharable metadata”, URL: http://www.oclc.org/content/dam/support/wcdigitalcollectiongateway/MetadataBestPractices.pdf). The current version of the schema is subject to changes as the functional requirements and workflow practices are evolving during the project experiences and prototype production.
Keywords: Open Access; DeepGreen; Metadaten